2021
DOI: 10.1016/j.cogpsych.2021.101406
|View full text |Cite
|
Sign up to set email alerts
|

Can humans perform mental regression on a graph? Accuracy and bias in the perception of scatterplots

Abstract: Despite the widespread use of graphs, little is known about how fast and how accurately we can extract information from them. Through a series of four behavioral experiments, we characterized human performance in "mental regression", i.e. the perception of statistical trends from scatterplots. When presented with a noisy scatterplot, even as briefly as 100 ms, human adults could accurately judge if it was increasing or decreasing, fit a regression line, and extrapolate outside the original data range, for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(57 citation statements)
references
References 76 publications
(98 reference statements)
13
31
0
Order By: Relevance
“…Second, we analyzed the effect of noise in the dataset. Previous studies of linear scatterplots (Ciccione & Dehaene, 2021) showed that, with increasing levels of noise, participants' extrapolations depart more from the statistical ideal. In the case of exponentials, it is not known whether the underestimation bias is already present for noiseless functions or if it only arises when extracting an exponential trend from noise.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Second, we analyzed the effect of noise in the dataset. Previous studies of linear scatterplots (Ciccione & Dehaene, 2021) showed that, with increasing levels of noise, participants' extrapolations depart more from the statistical ideal. In the case of exponentials, it is not known whether the underestimation bias is already present for noiseless functions or if it only arises when extracting an exponential trend from noise.…”
Section: Introductionmentioning
confidence: 90%
“…Using a terminology borrowed from machine learning literature (Geman et al, 1992), participants could be inaccurate in two ways: bias versus variance (Ciccione & Dehaene, 2021). Bias refers to the average error: a positive bias means that participants overestimate their extrapolation, whereas a negative bias means that they underestimate it.…”
Section: Evaluating Bias Versus Variance In Participants' Responsesmentioning
confidence: 99%
See 3 more Smart Citations